2020
DOI: 10.1111/rsp3.12329
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and unequal social distancing across demographic groups

Abstract: This paper analyses whether social distancing experienced by alternative demographic groups within the US has been different amid COVID-19. The formal investigation is achieved by using daily state-level mobility data from the US covering information on the demographic categories of income, education and race/ethnicity. The results show that social distancing has been experienced more by higherincome, higher-educated or Asian people after the declaration of National Emergency on 13 March 2020. Since alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
9
0
5
Order By: Relevance
“…That said, part-time workers in the United States experienced significantly less social distancing and proper hand washing than adults working full-time. Although the literature on the specific contributions of educational attainment and employment status on social distancing and hand washing is limited, our findings correspond with studies demonstrating significant associations between social determinants of health, such as education and employment, and practicing mitigation strategies to minimize risk of respiratory-related communicable diseases [ 21 , 26 , 37 39 ]. Overall, our results, interpreted in context of the existing literature, suggest that the impact of education and employment on COVID-related social distancing and hand washing may be more nuanced than the literature may indicate.…”
Section: Discussionsupporting
confidence: 84%
“…That said, part-time workers in the United States experienced significantly less social distancing and proper hand washing than adults working full-time. Although the literature on the specific contributions of educational attainment and employment status on social distancing and hand washing is limited, our findings correspond with studies demonstrating significant associations between social determinants of health, such as education and employment, and practicing mitigation strategies to minimize risk of respiratory-related communicable diseases [ 21 , 26 , 37 39 ]. Overall, our results, interpreted in context of the existing literature, suggest that the impact of education and employment on COVID-related social distancing and hand washing may be more nuanced than the literature may indicate.…”
Section: Discussionsupporting
confidence: 84%
“…But when coupled with the ability to purchase all necessary goods and services online, the decision to relocate further away becomes even more enticing. This is particularly true for wealthier, well‐educated individuals who are more likely to be able to work from home (Matson et al, Forthcoming; Yilmazkuday, 2020) but also, as demonstrated in this study, display the highest likelihood to shop online during the COVID‐19 pandemic. As such, many cities may experience an exodus as this segment of the population begins to find that the advantages of living in remote areas outweigh its disadvantages.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 51%
“…Regarding economic intuition behind the results, it is evident that consumption of products and services that can be consumed at home (e.g., grocery, pharmacy, home maintenance) have increased amid COVID-19, whereas consumption of products and services that cannot be consumed at home (e.g., fuel, transportation, personal care services, restaurant) have decreased. This approach is similar to the one that has been used to explain the reduction in economic activity, unemployment or social distancing experience by workers' ability of working from home as in studies such as by Dingel and Neiman (2020); Bick et al (2020) or Yilmazkuday (2020). The only difference is that it is consuming at home that can be connected to the sectoral heterogeneity in consumption changes amid COVID-19 as in this paper.…”
Section: Discussion On Estimation Resultsmentioning
confidence: 83%